Psychological Cognitive Development of the Main Character in Tangled (2010) Movie - Huang, Felicia; Suprayogi, Suprayogi (Institut Agama Islam Negeri Palopo, 2024)
This research explores the cognitive development of Rapunzel, the main character in Disney’s Tangled (2010), using Jean Piaget’s theory of cognitive development as a framework. Piaget's framework, based on stages—Sensori-motor, Preoperational, and Formal Operational are applied to analyze Rapunzel’s growth from a sheltered upbringing to self-discovery. The research employs a descriptive qualitative method, focusing on scenes and dialogue to track how her thinking develops. The research shows how Rapunzel learns to think logically, solve problems, and understand more complex ideas. Her journey from being innocent and influenced by her environment to becoming an independent thinker follows the stages of Piaget’s theory. By looking at her experiences, the reader can see how they challenge her understanding, help her become more independent, and lead her to a more mature way of thinking. Through this critical examination, the research highlights the relevance of Piaget’s theory in understanding character growth within narrative storytelling.